2008
DOI: 10.2460/javma.232.6.867
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam as an adjunct to phenobarbital treatment in cats with suspected idiopathic epilepsy

Abstract: Objective—To assess pharmacokinetics, efficacy, and tolerability of oral levetiracetam administered as an adjunct to phenobarbital treatment in cats with poorly controlled suspected idiopathic epilepsy. Design—Open-label, noncomparative clinical trial. Animals—12 cats suspected to have idiopathic epilepsy that was poorly controlled with phenobarbital or that had unacceptable adverse effects when treated with phenobarbital. Procedures—Cats were treated with levetiracetam (20 mg/kg [9.1 mg/lb], PO, q 8 h). After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 18 publications
(19 reference statements)
5
62
1
1
Order By: Relevance
“…A similar rate was reported for bromide, however associated with more adverse events including idiosyncratic allergic pneumonitis [25]. The only available data on levetiracetam as add-on therapy to phenobarbital reported 25–30% seizure freedom [26]. Our study demonstrated a rate of seizure freedom with imepitoin treatment similar to that previously reported for phenobarbital in cats.…”
Section: Discussionsupporting
confidence: 89%
“…A similar rate was reported for bromide, however associated with more adverse events including idiosyncratic allergic pneumonitis [25]. The only available data on levetiracetam as add-on therapy to phenobarbital reported 25–30% seizure freedom [26]. Our study demonstrated a rate of seizure freedom with imepitoin treatment similar to that previously reported for phenobarbital in cats.…”
Section: Discussionsupporting
confidence: 89%
“…Its novel mechanism of action coupled with minimal reported adverse effects makes it an appealing drug for seizure control in cats . Pharmacokinetics of intermediate‐release levetiracetam (IRL)‐administered PO in cats support a 20–25 mg/kg dosage, but the short elimination half‐life of 2.95 ± 0.95 hours necessitates a q8h dosing regimen, decreasing owner compliance . An extended‐release formulation of levetiracetam is specially formulated to result in a lower maximal drug concentration ( C max ), a longer time to maximal concentration ( T max ) and less fluctuation in serum concentrations in humans when compared to IRL .…”
mentioning
confidence: 99%
“…1 Causes of seizures and treatment options for cats are historically poorly described in the veterinary literature; however, there is a wealth of recently published clinical research focusing on feline seizures. 2,3,4,5,6,7 Underlying causes of seizures in cats are similar to those identified in dogs, although incidence varies between the two species, as do clinical manifestations of seizure activity. The goals of this article are to review recent veterinary literature related to feline seizures, with a focus on seizure classification, clinical manifestations, diagnostics, and treatment options.…”
Section: Introductionmentioning
confidence: 79%
“…7 LEV is well tolerated in cats, and the only adverse effects noted in a small clinical study were mild self-limiting inappetence and lethargy. 7 LEV is available in generic forms as an oral solution, oral tablet, and injectable preparation. The starting dose for LEV in cats is the same as for dogs, at 20 mg/kg orally.…”
Section: 40mentioning
confidence: 94%
See 1 more Smart Citation